The effect of differentiated learning method in teaching Arabic language on students’ motivation - Abdullah Meyad, Najiba; Roslan, Samsilah; Abdullah, Maria Chong; Maming, Pabiyah (Council for Innovative Research, 2014)
This paper investigates the effect of Differentiated Learning Method (DLM) on students’ motivation towards studying the Arabic language (AL) as a foreign language in Malaysia. The participants in this study were 100 (47 males and 53 females) Malaysian form four students attending secondary school in Kolej Islam Sultan Alam Shah (KISAS). They were selected for this study to determine the effect of DLM on their motivation towards studying AL. The pre-and post-questionnaire comparison groups design was used to determine if there were significant differences between the experimental and control groups. The experimental group was taught using DLM based on the Universal Design of Learning model (UDL) and Differentiated Instruction model (DI), while the control group was taught using the Teacher Centered Method (TCM). Descriptive statistics were used to determine the effect of DLM on students’ motivation towards studying AL. The statistical results demonstrated that there was a significant difference in the post-test between the experimental group (M=155.740, SD=12 .663) and the control group (M=145.280, SD= 14.405); t (3.856); p<.05). The experimental group was generally more motivated than the control group which proves that the DLM is an effective approach in improving students’ motivation towards studying the Arabic Language as a foreign language in Malaysia.